1995
DOI: 10.1172/jci117759
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric DNA in normal and leukemic blood cells.

Abstract: We studied telomeric DNA in leukemic cells as well as in normal T cells, B cells, monocytes, polymorphonuclear leukocytes, and bone marrow hematopoietic progenitor cells. No marked differences were observed in the sizes of the telomeric repeats in the various populations of normal blood cells obtained from donors in their twenties to sixties, and the telomere length ranged between 8.5 and 9.0 kb. The leukemic cells of 12 patients with acute leukemia (seven with myeloid and five with lymphoid leukemia) showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Our observations dispel a commonly held assumption regarding the timing of telomerase dysregulation in the leukemogenic process. In AML blasts, telomeres are generally shorter than those of normal cells (21,22), which has been thought to reflect up-regulation of telomerase expression only in the later stages of leukemogenesis after telomeres have shortened because of leukemic proliferation. Our finding of dissociation between telomerase activity and telomere length maintenance in hematopoietic cells indicates that telomerase up-regulation can be an earlier step in the leukemogenic program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations dispel a commonly held assumption regarding the timing of telomerase dysregulation in the leukemogenic process. In AML blasts, telomeres are generally shorter than those of normal cells (21,22), which has been thought to reflect up-regulation of telomerase expression only in the later stages of leukemogenesis after telomeres have shortened because of leukemic proliferation. Our finding of dissociation between telomerase activity and telomere length maintenance in hematopoietic cells indicates that telomerase up-regulation can be an earlier step in the leukemogenic program.…”
Section: Discussionmentioning
confidence: 99%
“…Solid tumors arising in telomerase-negative tissues typically circumvent this barrier by inactivation of checkpoints triggered by loss of telomere function and eventually by activation of telomerase expression. Although acute myelogenous leukemia (AML) is thought to originate in telomerase-expressing HSC (19,20), telomeres in AML blasts are generally shorter than those in normal cells (21,22), suggesting that as in normal HSC, telomerase in leukemic stem cells does not prevent proliferationassociated loss of telomeric DNA. Nevertheless, high levels of telomerase activity are present in Ͼ70% of AML cases (23).…”
mentioning
confidence: 99%
“…16 However, recent precise studies demonstrated a significant difference between T cells and neutrophils. Moreover, memory T cells are shown to have shorter telomeres than those of naive T cells.…”
Section: Discussionmentioning
confidence: 99%
“…After quantitative system of telomerase activity was established, approximately 75% of the patients with acute leukemia showed elevated levels of telomerase activity. Telomere length was generally shortened (Takeuchi et al, 1994;Yamada et al, 1995;Ohyashiki et al, 1997a). A high level of telomerase activity (more than 10-fold compared to normal hematopoietic cells) was noted in both AML and ALL (Counter et al, 1995;Broccoli et al, 1995;Zhang et al, 1996;Ohyashiki et al, 1997a;Li et al, 2000;Engelhardt et al, 2000).…”
Section: Acute Leukemiasmentioning
confidence: 99%